On the dust deposition and its effects on heat transfer in absorber pores of an open volumetric air receiver - Upadhyay V.K.; Singh G.; Chandra L.; Bandyopadhyay B. (My University, 2025)
The deposition of dust in the absorber pores of an open volumetric air receiver (OVAR) offers a significant challenge in arid deserts. In this paper, to address this problem, two aspects are investigated, (i) the transport of an isolated dust particle in a straight, circular absorber pore, for a steady, thermally-hydraulically developing, laminar flow, and (ii) the consequences on heat transfer due to dust particles accumulation, in a straight, circular, absorber pore. The first problem is investigated with a semi-analytical approach and the second problem makes use of computational fluid dynamics simulations. The finding shows (a) a heat flux may be beneficial, for mitigating the dust deposition in a, straight, circular, clean absorber pore, (b) dust deposition in a straight, circular, absorber pore is detrimental to heat transfer, which may lead to its failure, (c) the thermal development length will be reduced for the dust deposited pore in comparison to a clean pore. The findings reveal a way of mitigating dust deposition in a clean pore, and the need for a cleaning strategy of dust deposited absorber pore, for sustainable operation of an open volumetric air receiver. © 2020 International Solar Energy Society